(untitled) (SAARC Journal of Agriculture, 2022)
A noticeable variation is present among the guava (Psidium guajava L.) genotypes available in Bangladesh. Thirty-three (25 indigenous, 5 released, and 3 exotic) genotypes of guava were used in ex-situ conditions from different locations of Chattagram, Brahmanbaria, Pirojpur, and Gazipur districts and assessed based on 10 traits to know their genetic diversity. The measured traits were number of flowers, fruits, harvested fruits per plant, single fruit weight (g), number of seeds/fruits, thousand seed weight (g), vitamin C, total sugar content, and fruit yield/plant (kg). Twenty-one genotypes showed 100-400 g of single fruit weight, and 12 showed 20-100 g. The genotype G14 (BARI Peyara-1) produced the highest fruit yield/plant (131.04 kg) followed by G24 (PG Muk-005) and G 23 (PG Muk-005) yielded 65.49 kg and 64.62 kg, respectively. Twenty-one genotypes showed above 250 mg/100g vitamin C content. Above 42% (14 genotypes) contained total sugar content of over 5%. The first two axes accounted 58.8% of the total variation among 10 traits. Based on the heatmap analysis, cluster-IV represents a high value containing the number of flowers, fruits, and harvested fruits per plant. The genotypes G 14, G17 (BARI Peyara-4), G21 (PG Sit-003), G23, G24, and G29 (Thai Peyara-3) might be considered the best based on the morpho-biochemical characteristics. Many traits are of significant economic importance and could be used as breeding targets to increase yield and quality. Therefore, variation among guava genotypes will be an excellent source for future crop improvements. SAARC J. Agric., 20(1): 15-28 (2022)